Pendekatan Discovery Inquiry Pada Pembelajaran Fikih - Yadain, Zul (Al-Riwayah : Jurnal Kependidikan, 2017)
The high or low level of learning activities are influenced by the approach used by the teacher. There are at least two approaches, namely oriented approach to the teacher or so-called the teacher-oriented and student-oriented approach or the socalled student centered. The first approach is called autocratic type and the second approach is called democratic type. One of them is inquiry approach. Inquiry is a way of presenting the many lessons that engage students in mental processes of the invention framework. Inquiry emphasis on the process of finding their own answers by the observations, ask questions, submit allegations, data collection and concluded, all of which require scientific methodology. With this strategy, students are expected to find the true facts of observation, conjecture, until inference. This approach is to discover as a part of the inquiry. The inquiry is an expansion of the process of discovery that is used in more depth, the inquiry is in English inquiry, means the inquiry or examination, investigation, the inquiry as a process of the common man to seek and understand information. This approach is opposite of the view that students as subjects and objects in the study, having the basic ability to develop optimally according to ability.